2012
DOI: 10.1038/oby.2011.383
|View full text |Cite
|
Sign up to set email alerts
|

Postmenopausal Sex Hormones in Relation to Body Fat Distribution

Abstract: Being overweight or obese increases the risk of postmenopausal breast cancer. A potential reason may be the frequently observed positive association of BMI with endogenous sex hormones and its negative association with sex hormone‐binding globulin (SHBG). The purpose of this study was to investigate whether a woman's body fat distribution shows a BMI‐independent association with these breast cancer‐related biomarkers. Performing cross‐sectional analyses among 1,180 postmenopausal women, we assessed whether ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
70
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 38 publications
4
70
2
1
Order By: Relevance
“…This fat distribution is similar to that reported previously [28][29][30][31], reflecting the contribution of sex hormone profiles to the accumulation of abdominal fat.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This fat distribution is similar to that reported previously [28][29][30][31], reflecting the contribution of sex hormone profiles to the accumulation of abdominal fat.…”
Section: Discussionsupporting
confidence: 74%
“…Moreover, postmenopausal women not using HRT may limit intra-abdominal adipose tissue accrual due to the higher circulating free testosterone [30]. Another study showed conflicting results, demonstrating that after menopause, an abdominal yet not gluteofemoral fat distribution is associated with high levels of free estradiol and free testosterone and with low levels of sex hormone-binding globulin [31]. Further studies are therefore needed to elucidate the mechanism by which sex hormones profiles regulate a lipid deposition in postmenopausal women and the extent to which HRT may affects these relationships.…”
Section: Discussionmentioning
confidence: 92%
“…In postmenopausal women, the primary production of estrogen occurs in the adipose tissue via aromatization of androstenedione to estrone, such that levels of bioavailable estrogen are greater in obese than lean women (41). The ratio of estradiol to testosterone may also be relevant (42).…”
Section: Biologic Mechanismsmentioning
confidence: 99%
“…The question is to what extent do the sex hormone levels contribute independently? It has been reported that sex hormone levels are positively related to the total amount of fat tissue, with an inverse relation to sex hormone binding globulin [4]. So it is not unlikely that in the current study the observed higher oestrogen levels are an association with known risk factors that lead to MI rather than being causative.…”
mentioning
confidence: 37%